Preliminary findings of sustainable interior design criteria in hotel industry to the performance impact and hedonic consumption / Siti Noorfairus Che Abdullah ... [et al.] - Che Abdullah, Siti Noorfairus; Khalil, Natasha; Harun, Siti Norsazlina; Hamid, Md Yusof; Abdullah Sani, Suwaibatul Islamiah (2022)
Hotels are significant for the tourism industry and constitute pillars of sustainable tourism. Among the concern factors in maintaining the hotel industry is the tangible value such as aesthetic appearance, interiors, room decorations, and furnishings. Ideally, the hotel industry relies on customer satisfaction towards the service. Customer satisfaction on the aesthetics and products of the hotel's interiors are viewed as hedonic. Hence, fulfilling the hedonic consumption is crucial for hotel's facilities management. Nevertheless, the sector also has an adverse impact on the environment. Sustainability issues on the maintenance management of aesthetic performance, service hospitality and awareness on sustainable interiors products are significant concerns in the hotel's performance effectiveness. Therefore, this study aims to identify the components of sustainable interior design requirements relating to facilities management in performance effectiveness and hedonic consumption. A qualitative method using semi structured interview was carried out in the preliminary phase of this study, involving three survey participants (architect, interior designer, GBI facilitator) that have experience in designing various green hotels. The data is analysed using ATLAS.ti9© qualitative software. The findings revealed that there are seven (7) sustainable ID criteria consists of biophilic, energy efficiency, water consumption, health and social flexibility, environmental comfort, ergonomics, and green awareness. The survey participants agreed that all of these criteria are related to a hotel's performance effectiveness in functional performance, environmental performance, technical performance and social performance. While for hedonic consumption, the sustainable ID is impacted to the hedonic elements in customer's mood, happiness, preferences and enjoyment. This study is significant to help the hotel industry managers identify which aspects of the property are critical to successful performance by integrating facilities management to the sustainable interior design requirements.